Molecular characterization of potentially virulent multidrug-resistant Enterococcus faecalis isolated from acquired urinary tract infections in Egyptian patients - Ahmed, Heba; Mostafa, Nagham; Elariny, Eman; Ahmed, Rania (Archives of Biological Sciences, 2023)
Paper description: Enterococcus faecalis was detected in 28% urine samples of hospitalized Egyptian patients with urinary tract infections (UTIs). E. faecalis infection was more frequent in females than males and most common in ages ≥41 with increased frequency of infection in rural regions. The genes encoding the virulence determinants in E. faecalis strains (cylA, cylB, cylM, gelE, esp, efaA, asa, ace) were determined using real-time PCR. Most E. faecalis strains were multidrug resistant and 56% of strains were biofilm-producers. Multidrug resistance of E. faecalis, their virulence potential and biofilm formation ability are a public health risk to UTI patients. Abstract: In this study, 154 urine samples were collected from urinary tract infections (UTIs) of hospitalized patients, with 43 (28%) positive for the presence of Enterococcus faecalis without detection of Enterococcus faecium. Based on the demographic data associated with UTI patients, the prevalence of E. faecalis among females was higher than among males in the age group ≥41 years; cases from rural areas showed higher infection than from urban localities. Patients not treated with antibiotics were 2.8-fold more likely to be infected with E. faecalis than patients who received antibiotics. At the molecular level, the genes encoding the virulence determinants in E. faecalis, including cytolysins (cylA, cylB and cylM), gelatinase (gelE), E. faecalis antigen A (efaA), extracellular surface protein (esp), aggregation substance (asa) and collagen binding adhesion (ace) were determined using SYBR green real-time PCR. Antibiotic susceptibility testing showed that almost all strains were multidrug-resistant, with an average multiple antibiotic resistance (MAR) index of 0.55. The colorimetric microtiter plate assay showed that 56% of the strains were biofilm producers. A significant correlation was observed between strong biofilm formation and the presence of cylB and cylM genes. Multidrug-resistant E. faecalis and its virulence potential and biofilm formation ability pose a risk to UTI patients.